Intestinal Behçet's and suspected intestinal Behçet’s disease: a report of four surgical cases - Rika Ono; Tetsuro Tominaga; Takashi Nonaka; Yuma Takamura; Kaido Oishi; Toshio Shiraishi; Shintaro Hashimoto; Keisuke Noda; Terumitsu Sawai; Shinji Okano; Takeshi Nagayasu (Surgical Case Reports)
Abstract Background Intestinal Behçet's disease (BD) is often associated with ulceration that requires surgery, including perforation and abscess formation. However, no consensus has been reached on the optimal extent of resection or treatment strategy. This study reviewed four cases of intestinal or suspected intestinal BD. Case presentations In Case 1, a 74-year-old woman diagnosed with BD 2 years earlier was treated with anti-tumor necrosis factor α antibody (Infliximab) and steroids. She had oral and pubic ulcers. After close investigation of abdominal pain, perforation of the gastrointestinal tract was suspected and surgery was performed. Multiple perforating ulcers and abscesses were found in the distal ileum, and the small intestine was resected. Postoperatively, the patient was treated with an increased steroid dose and symptoms have remained stable. Case 2 involved a 69-year-old woman with oral and pubic ulcers, ocular ulcer, and skin lesions. She experienced sudden onset of abdominal pain during treatment for lymphoma. She showed multiple perforating ulcers throughout the ileum and underwent resection of the small intestine and ileostomy. Upper abdominal pain appeared during postoperative treatment for high-output syndrome. The patient underwent omentoplasty after perforation of the upper gastrointestinal tract was diagnosed. Postoperatively, anti-interleukin-1 beta antibodies (canakinumab) was administered to control the disease. Case 3 involved an 81-year-old, previously healthy woman. She presented to her previous physician with complaints of pubic ulcer, hemorrhage and abdominal pain. Colonoscopy showed multiple ulcers throughout the entire colon. Steroid therapy was started, but bleeding proved difficult to control and total proctocolectomy was performed. Histopathology revealed multiple perforating ulcers and BD was diagnosed. Postoperatively, the patient remains under steroid control. Case 4 involved a 43-year-old man with abdominal pain who showed abscess formation in the ileocecal region. After excision of the ileocecal area, multiple ulcers were diagnosed. Two years later, abdominal pain recurred and free air was found in the abdomen on close imaging. Emergency anastomotic resection was performed due to ulceration and perforation of the anastomosis. Conclusions Intestinal BD may flare up after surgical treatment and require multiple surgeries. Introducing pharmacotherapy as soon as possible after surgical treatment is important to control the disease.